Vandalisme Koleksi di Unit Pelayanan Teknis (UPT) Perpustakaan Universitas Bengkulu - Isran Elnadi (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The effect of vandalism was the loss of the beauty of the book, damaged of paper, the loss of the information of the book thus reducing the comfort of reading. The problems of this study were (1) what is the causes of vandalism collection, (2) what is the weaknesses of librarian and staff so the occurrence of vandalism collection, (3) what is the solution to avoid of vandalism. The method of this study was descriptive qualitative. The populations of this study were the circulation collection at the second floor from 000 classifications (public in general) to 900 classifications (history and geography) that had vandalism by the librarian. Data collection of this study divided into two aspects, (a) primer data, (b) secondary data). The result of this study was for public in general (000) there was 1.700 copies (31.75) had vandalism with the type of the book crossed out, highlighter, torn, and underline. Philosophy of collection (100) that vandalism was 61 copied (1.65). Religion collection (200) 171 copies indicated vandalism. Social science (300) 68 copies indicated vandalism (0.3). Linguistics (400) 108 copies indicated vandalism (2.74). Pure Science (500) indicated vandalism 68 copies (0.71%). Collection of applied sciences (600) indicated vandalism 178 copied (0.999%). Art and sport (700) indicated vandalism 7 copies (0.379). Literature (800) indicated vandalism 141 copies (3.484%). History and Geography (900) indicated vandalism 141 copies (3.484%). The causes of vandalism collection, such as: Peer influence, parents often gives bad example to their children like throwing the trash out of place. Mass Media, the attitude of not taking care of the community to the act vandalism, lack of supervision of staff or librarians against the user/visitor.